Procalcitonin: How a hormone became a marker and mediator of sepsis - Beat P. Müller‐Stich; Kenneth L. Becker (2001)
Calcitonin was discovered in the early 1960s [1], at which time it was assumed to be a single hormone with a yet-to-be-determined role in human physiology. Since then it has been found to be only one entity among a large array of related circulating peptides, at least one of which has a pivotal role in the host response to microbial infections [2, 3]. The aim of this review is to describe this metamorphosis of an endocrine hormone to a new class of hormokine mediators in infectious diseases.